The Role of Physical Education and Sports in the Daily Activities of Students Who are Studying in Pedagogy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Based on the research, the article reveals the role of physical culture and sports in the daily activities of students of pedagogical directions. It has been established that students who do not engage in physical culture or sports have indicators characterizing physical capabilities at a lower level than athletes engaged in sports, and these indicators decrease even more both at the end of the academic year and during the transition from course to course.